Effect of food-related stress conditions and loss of agr and sigB on seb promoter activity in S. aureus. (August 2017) - Sihto, Henna-Maria; Stephan, Roger; Engl, Christoph; Chen, John; Johler, Sophia
Abstract: Staphylococcal enterotoxin B (SEB) causes staphylococcal food poisoning and is produced in up to ten times higher quantities than other major enterotoxins. While Staphylococcus aureus growth is often repressed by competing flora, the organism exhibits a decisive growth advantage under some stress conditions. So far, data on the influence of food-related stressors and regulatory mutations on seb expression is limited and largely based on laboratory strains, which were later reported to harbor mutations. Therefore, the aim of this study was to investigate the influence of stress and regulatory mutations on seb promoter activity. To this end, transcriptional fusions were created in two strains, USA300 and HG003, carrying different seb upstream sequences fused to a blaZ reporter. NaCl, nitrite, and glucose stress led to significantly decreased seb promoter activity, while lactic acid stress resulted in significantly increased seb promoter activity. Loss of agr decreased seb promoter activity and loss of sigB increased promoter activity, with the magnitude of change depending on the strain. These results demonstrate that mild stress conditions encountered during food production and preservation can induce significant changes in seb promoter activity. Highlights: NaCl, nitrite, and glucose stress decrease seb promoter activity. Lactic acid stress (pH 6.0) leads to increased seb promoter activity. Loss of agr decreases and loss of sigB increases seb promoter activity. seb promoter activity is not dependent on 1 kb sequence upstream of seb .